Temperature Effect on Human Erythrocyte Membrane Permeability for 1,2-Propane Diol and Dimethylsulfoxide - Gordiyenko, O. I. (Problems of Cryobiology and Cryomedicine, 2003)
The paper presents the results of study of human erythrocyte membrane permeability for 1,2-propane diol (1,2-PD) and dimethylsulfoxide (DMSO) within temperature limits of 3-37ï‚°C. Arrhenius dependencies of permeability coefficients for the studied substances were shown to be underwent the series of breaks within the following temperature limits: 8-12, 18-20 and 28-30ï‚°C (being known as the critical ones for some functional indices of biological membranes) with sharp changes in activation energy (EA). Some possible mechanisms of thermoinduced changes in parameters of non-electrolytes permeation via erythrocyte membrane are discussed.